2012
DOI: 10.1002/jwmg.283
|View full text |Cite
|
Sign up to set email alerts
|

Stopover duration of fall‐migrating dabbling ducks

Abstract: The amount of time migrating birds spend at stopover sites, or stopover duration, partially determines an individual's access to resources, the environmental conditions encountered, and the exposure to predation, which in turn affect survival and fecundity. As such, migratory behaviors such as stopover duration can have a considerable effect on populations of migrants and plans for their conservation. This is especially true for migrant waterfowl, which are explicitly conserved through Joint Venture (JV) partn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 56 publications
1
40
1
Order By: Relevance
“…However, we documented relatively low use (18.7%, diurnal; 18.1%, nocturnal) of designated refuges by mallards in our study area. Although we did not measure food density on refuges in our study area, data from aerial waterfowl inventories and our observations suggested that foraging habitat was generally poor on these areas (O'Neal et al , Hagy et al ). Flooding from the Illinois River in August and thereafter killed or prevented maturation of moist‐soil plants or affected infrastructure used for managing hydrology and moist‐soil vegetation.…”
Section: Discussionmentioning
confidence: 88%
“…However, we documented relatively low use (18.7%, diurnal; 18.1%, nocturnal) of designated refuges by mallards in our study area. Although we did not measure food density on refuges in our study area, data from aerial waterfowl inventories and our observations suggested that foraging habitat was generally poor on these areas (O'Neal et al , Hagy et al ). Flooding from the Illinois River in August and thereafter killed or prevented maturation of moist‐soil plants or affected infrastructure used for managing hydrology and moist‐soil vegetation.…”
Section: Discussionmentioning
confidence: 88%
“…Numerous techniques have been used to quantify the timing and duration of migration in waterfowl, including radar [19] and radio-telemetry [20]. Although the study of migration chronology has been historically limited spatially and temporally, new technologies and methods have enabled researchers to develop quantitative techniques to define migration at the individual level [26], [27], [43].…”
Section: Discussionmentioning
confidence: 99%
“…Waterfowl migration has been examined using a variety of methods, including counts [18], radar [19], and very high frequency (VHF) radio-telemetry [20]. Despite these efforts to document migration chronology, past studies have been limited spatially (counts, VHF radio-telemetry), temporally (radio-telemetry, banding), or taxonomically (radar) by available technology.…”
Section: Introductionmentioning
confidence: 99%
“…), whereas another study in North America estimated a mean stopover duration of 12 days (Krementz, Asante & Naylor ). Finally, a study that examined stopover duration of dabbling ducks using weather radar in Illinois, USA, documented a mean value of 28 days (O'Neal, Stafford & Larkin ). Mean stopover duration for present conditions in our model was 19·53 days, which is within the range of values observed in these empirical studies.…”
Section: Methodsmentioning
confidence: 99%